Anti-c-myc RNAi-Based Onconanotherapeutics - Saffiya Habib; Mario Ariatti; Moganavelli Singh (Biomedicines, 2020)
Overexpression of the c-myc proto-oncogene features prominently in most human cancers. Early studies established that inhibiting the expression of oncogenic c-myc, produced potent anti-cancer effects. This gave rise to the notion that an appropriate c-myc silencing agent might provide a broadly applicable and more effective form of cancer treatment than is currently available. The endogenous mechanism of RNA interference (RNAi), through which small RNA molecules induce gene silencing by binding to complementary mRNA transcripts, represents an attractive avenue for c-myc inhibition. However, the development of a clinically viable, anti-c-myc RNAi-based platform is largely dependent upon the design of an appropriate carrier of the effector nucleic acids. To date, organic and inorganic nanoparticles were assessed both in vitro and in vivo, as carriers of small interfering RNA (siRNA), DICER-substrate siRNA (DsiRNA), and short hairpin RNA (shRNA) expression plasmids, directed against the c-myc oncogene. We review here the various anti-c-myc RNAi-based nanosystems that have come to the fore, especially between 2005 and 2020.